Antioxidants and Improvement of Immune System Function in HIV infected Patients: A Review Article - Narges Jani; Ghasem Yadegarfar; Maryam Hajishafiyee; Leila Azadbakht (مجله دانشکده پزشکی اصفهان, 2011)
Background: World’s statistics show the fast growth of prevalence of Human Immunodeficiency Virus (HIV) in all over the world. A great deal of studies relevant to the all effective factors of HIV/AIDS (Acquired immune deficiency syndrome), some parts of them related to nutrition. Disability to eat and digest foods and to absorb nutrients from food is one of the results of weakness and wasting of all HIV infected patients. This kind of weakness affects to intensification of signs of disease and increase risk of opportunistic infections. Nutritional and metabolic factors significantly affect morbidity and mortality of HIV/AIDS patients. The progression of disease in human body is causing to stimulate the immune system and increase the oxidative stress and also decrease the antioxidants level of plasma. Consequently using diversity diet or antioxidant supplementation as an effective and no expensive treatment is useful along the other clinical treatments to improve immune system and welfare the patient’s status. In this review article we try to examine studies which are related to the effect of antioxidants on the immune system and finally the effects of them on progression of disease in HIV infected patients.